PENGARUH KONSUMSI OBAT ANTIHIPERTENSI TERHADAP LAJU SEKRESI SALIVA PADA LANSIA DI DAERAH PEDESAAN (Kajian pada Anggota Posyandu Lansia di Dusun Sanggrahan, Sleman, Yogyakarta) - , ASTRID ARDIANA ARMANTO, drg. Bernadetta Esti Chrismawaty, M.Kes, M.D.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aging process affects various body systems, both physiologically and pathologically. Changes that occur in the cardiovascular system are usually a thickening of the walls of blood vessels resulting in increased blood pressure or hypertension. Antihypertensive drugs are commonly given to treat hypertension condition. Decrease in salivary gland secretion is one of the side effects of antihypertensive drugs. An elderly who live in rural areas have limited health information than elderly living in urban areas. It is influenced by various factors such as socioeconomic, education, and culture. This study aimed to determine the effect of antihypertensive medication on the salivary secretion rate in the rural elderly. This study was cross-sectional analytical observations conducted in 30 rural elderly with hypertension. The subjects were divided into 2 groups: 15 subjects with antihypertensive medication and 15 subjects without antihypertensive medication. The collections of unstimulated saliva were performed by spitting method. The salivary secretion rate differences between groups were analyzed descriptively and analytically through Mann-Whitney test. The descriptive analysis showed a mean of salivary secretion rate in group with antihypertensive medication lower (0.099 Â± 0.050 ml/min) than group without antihypertensive medication (0.156 Â± 0.117 ml/min), however the analytical analysis by Mann-Whitney test showed no significant differences between both (p=0.065). Based on the result, it can be concluded that the antihypertensive medication affects the salivary secretion rate, but there is no statistically significant differences on salivary secretion rate between rural elderly hypertensive patients with and without antihypertensive medication.